2018
DOI: 10.1273/cbij.18.44
|View full text |Cite
|
Sign up to set email alerts
|

<b>Binding properties between curcumin and malarial tubulin: molecular-docking and </b><i><b>ab initio</b></i><b> fragment molecular orbital calculations</b>

Abstract: Curcumin can bind to tubulin and inhibit the formation of tubulin polymer, which contributes to the formation of microtubule. Binding sites of curcumin on the α-and β-tubulin heterodimer were predicted by a molecular docking study to ascertain probable causes for the observed anti-microtubule effects of curcumin. However, the specific interactions between curcumin and the tubulins have yet to be elucidated at an electronic level. We here investigated the binding properties between curcumin and α-or β-tubulin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The solvated interaction energy (SIE) method is a fast calculation with moderate accuracy. Based on the divide and conquer algorithm [30], the fragment molecular orbital (FMO) method can provide the detailed interaction energies with high accuracy [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…The solvated interaction energy (SIE) method is a fast calculation with moderate accuracy. Based on the divide and conquer algorithm [30], the fragment molecular orbital (FMO) method can provide the detailed interaction energies with high accuracy [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism for the antitumor activity of natural compound curcumin were related with multiple signaling pathways, such as the signal transducer, nuclear factor-κB, cyclooxygenase 2, mitogen-activated protein kinase, and activator of transcription 3, and TNF-α signaling pathways. Curcumin is a spectrum inhibitor that targets epidermal growth factor receptor ( Gopal, 2022 ), protein kinase C ( Hasmeda and Polya, 1996 ), tubulin ( Chakraborti et al, 2011 ; Ota et al, 2018 ), cyclin-dependent kinase 2 ( Sumirtanurdin et al, 2020 ), casein kinase 2 ( Cozza et al, 2020 ), adenosine monophosphate-activated protein kinases ( Soltani et al, 2019 ), and Abelson leukemia virus tyrosine kinase 1 ( Rodrigues et al, 2021 ). A previous study reported that curcumin exhibits antitumor activity in triple-negative breast cancer patient-derived xenograft tumor mice by inhibiting the expression of salt-inducible kinase 3 (SIK3) ( Cheng et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is a fact that many of existing now malaria therapeutics are increasingly ineffective and it is an urgent need in development of principally new therapeutic strategies and agents. During last ten years there has been a new growth of interest in tubulin as an important antiprotozoan target [6,7] Several classes of microtubule (MT) inhibitors have demonstrate potent activity against malarial parasites in in vivo: vinblastine [8][9][10], dolastatin 10 [11], auristatins [12] and taxoids [13,14]. Most of these agents have been demonstrated to disrupt or stabilize normal microtubular structures.…”
mentioning
confidence: 99%